A new genus and a new species of phytoseiid mite (Acari: Phytoseiidae) from northeastern Brazil - Fiaboe, K. K.m.; de Moraes, G. J.; Gondim Jr, M. G.c. (Zootaxa, 2004)
A new genus and a new species of phytoseiid mite, Tenuisternum bahiense n. g., n. sp., collected from Solanum paludosum Moric (Solanaceae), is described from the State of Bahia, northeastern Brazil.